S, Se and Te contents of basalts from the Reykjanes Ridge and SW Iceland Rift Zone (IEDA: EarthChem Library)
This data set reports S, Se, and Te concentrations in basaltic whole-rocks and glasses from the SW Iceland rift zone, including sub-glacial glasses, and submarine lavas from the Reykjanes Ridge, Gibbs Fracture Zone, and Mid-Atlantic Ridge. We thank R. Kingsley, J.M. Rhodes, and C. Mandeville for assistance with analyses. This work was supported by NSF award OCE# 0326658 to JGS. NSF award OCE# 1555523 provides curatorial support for marine geological samples at the Graduate School of Oceanography, University of Rhode Island.